Platelet Count and Platelet Indices in Patients with Stable and Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis. (4th March 2021) - Zinellu, Angelo; Paliogiannis, Panagiotis; Sotgiu, Elisabetta; Mellino, Sabrina; Fois, Alessandro G.; Carru, Ciriaco; Mangoni, Arduino A.
Abstract: Platelets play an important role in the pathophysiology of chronic obstructive pulmonary disease (COPD) by mediating thrombotic, inflammatory, and immune processes in the lung. We conducted a systematic review and meta-analysis of studies investigating the platelet count and three platelet indices, mean platelet volume (MPV), platelet distribution width (PDW), and platelet to lymphocyte ratio (PLR) in stable COPD vs. non-COPD patients and in stable COPD vs. acute exacerbation of COPD (AECOPD) patients (PROSPERO registration number: CRD42021228263). PubMed, Web of Science, Scopus and Google Scholar were searched from inception to December 2020. Twenty-seven studies were included in the meta-analysis, 26 comparing 4, 455 stable COPD patients with 7, 128 non-COPD controls and 14 comparing 1, 251 stable COPD with 904 AECOPD patients. Stable COPD patients had significantly higher platelet counts (weighted mean difference, WMD = 13.39 x10 9 /L, 95% CI 4.68 to 22.11 x10 9 /L; p < 0.001) and PLR (WMD = 59.52, 95% CI 29.59 to 89.44; p < 0.001) than non-COPD subjects. AECOPD patients had significantly higher PLR values than stable COPD patients (WMD = 46.03, 95% CI 7.70 to 84.35; p = 0.02). No significant differences were observed in MPV and PDW. Between-study heterogeneity was extreme. In sensitivity analysis, the effect size was not modified when each study was sequentially removed. The was no evidence of publication bias. In our meta-analysis, specific platelet biomarkers were associated with stable COPD (platelet count and PLR) and AECOPD (PLR). However, the observed heterogeneity limits the generalizability of the findings. Further studies are required to determine their prognostic utility and the effects of targeted interventions in COPD.